The Influence of Spirituality through Indian Vedic Scriptures on Modern Business Leadership and Decision Making in Indian Business Enterprises - Jaishur, Jansher Madathiparambil (2013)
The role of a decision maker in an organization is often influenced by the internal and external factors which make things even more complex. As he needs to meet the preset goals of the company; and moreover even the personal values, faith and au fait also dominates the decision making process and could predict the outcome of the decisions made. Religion and spirituality could be highly influential, as one’s individual characteristic is molded by his religious beliefs and dominate the outcome of the decisions made and there is a strong correlation between leadership and inner values of an individual. However, there is still uncertainty about the various ways by which spirituality could influence in one’s decision making, due to the lack of empirical evidence. It is clearly evident that organizations in India which uses spiritualistic principles in decision making are not implementing the framework Indian Vedic scriptures as they have not accommodated to it. Moreover firms which do not use the right spiritual factors in decision making and leadership tends to fail in wrong run. This dissertation attempts to explain how spirituality could influence Indian business leaders in making the right decisions in their respective business organizations and whether the principles of the Bhagvad Gita (Indian Veda) could be implemented in the prevailing decision making practices in India through qualitative analysis.